Visit of President Dr. A.P.J. Abdul Kalam to Myanmar and Mauritius, 8 to 13 March 2006 - Abdul Kalam, A. P. J. (Avul Pakir Jainulabdeen), 1931-2015 (Public Diplomacy Division, Ministry of External Affairs, 2006)
Selected speeches of the President of India during his visits to the Burma and Mauritius in 2006.